(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
The case of the Decentralized Public Organization for the Provision of Drinking Water Services in a Mexican municipality that is characterized by its water complexity is reviewed: it’s there the two most important water extraction systems in the country, in this territory there are two operating agency, and because it is located on the second most important basin, the Alto Lerma basin. The theoretical approach is the institutional design from the new economic institutionalism. The study is carried out from a qualitative approach to analyze the perception of the users of the drinking water service, through a questionnaire that takes up the principles of institutional design: review, solidity, sensitivity and feasibility; and articulates them with aspects of the law: normative universality, availability, quality and accessibility. The results show a negative perception in all the principles evaluated, greater participation was obtained from the region with the greatest social backwardness and where access to the service is not fulfilled in accordance with the human right to water. It is proposed to change the water user figure for water responsibility, this is in the vision of natural goods and moves away from the economic perspective of natural resources.